Applying fuzzy logics in net present value calculation for construction projects - Nguyễn Hoài Nghĩa (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ, 2012)
In practice, engineering economic analysis involves uncertainty about future cash flows. Therefore, the conventional cash flow models where cash flows are defined as either crisp numbers or risky probability distributions do not describe sufficiently the nature of future cash flows. As an alternative to conventional cash flow models, this arti-cle proposes an engineering economic decision model in which the uncertain cash flows and discount rates are specified as triangular fuzzy numbers. Fuzzy set theory, with the advantages in dealing with vagueness in human thoughts and perceptions, proves its fit-ness in solving the problem than the conventional cash flow models. The present value formulation of this fuzzy cash flow model is derived in this article. The result of the fuzzy present value is compared with the value that is caculated by probability theory. The fuzzy present value is a fuzzy number with nonlinear membership function.